9 - Revue des livres: A propos de «mouvements ouvriers et crise économique» Réponse à 0. Faye: by Alfred I. Ndiaye, Bassirou Tidjani - Tidjani, Bassirou; Alfred I. Ndiaye (Africa Development, 1997)
Abstract